1987
DOI: 10.1111/j.1365-2672.1987.tb02395.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of thermophilic campylobacters in a river system

Abstract: Fifteen kilometres of a river system traversing rural and urban areas and subject to sewage works effluent discharge was studied during a 12 1/2 month period. A total of 312 samples was collected from 12 sites at 14 d intervals and tested by a glass microfibre filtration method and a most probable number (MPN) method. Campylobacters were found in 43% of samples by the filtration method and 21% by the MPN method. The lowest frequency of isolation and lowest counts (less than 10 campylobacters/100 ml) were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
2

Year Published

1988
1988
2006
2006

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 18 publications
6
84
2
Order By: Relevance
“…In this study all patients with elevated campylobacter antibody titres, including those who had not attended the blood donation, had at least fourfold or greater antibody titre changes in consecutive sera. In vitro studies have demonstrated that Campylobacter sp. remain viable for months in surface water at 4°C, and appear to survive best in water obtained from high mountain streams (Blaser et al 1980;Gondrosen, 1986 and winter (Bolton et al 1987) when the water is cold. In this outbreak either the Campylobacter sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study all patients with elevated campylobacter antibody titres, including those who had not attended the blood donation, had at least fourfold or greater antibody titre changes in consecutive sera. In vitro studies have demonstrated that Campylobacter sp. remain viable for months in surface water at 4°C, and appear to survive best in water obtained from high mountain streams (Blaser et al 1980;Gondrosen, 1986 and winter (Bolton et al 1987) when the water is cold. In this outbreak either the Campylobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…While some have found campylobacters regularly from many surface waters (Knill, Suckling & Pearson, 1982;Taylor, Brown & McDermott, 1982;Pearson et al 1985;Bolton et al 1987) but others have not (Perkins-Jones, Holman & Frost, 1982). There is evidence of faecal contamination in water when campylobacter are present (Knill, Suckling & Pearson, 1982) as in this study, but correlation with faecal indicators is not clear (Perkins-Jones, Holman & Frost, 1982;Carter et al 1987), possibly due to the relatively low numbers of campylobacters in water.…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter infection in humans is generally highest in summer (Skirrow, 1987), and it is possible that subsequently high levels of environmental contamination with campylobacter in autumn is reflected in the gull population. However, an alternative, and perhaps more likely, explanation of the peak in carriage rates in gulls is that this relates to the higher winter prevelance of campylobacter in natural waters, which has been attributed to their longer survival at cooler temperatures (Blaser et al 1980;Reisinger, 1985;Bolton et al 1987;Carter et al 1987). The drinking of contaminated water at winter roosting sites (to which the gulls themselves will contribute campylobacter) may increase carriage rates.…”
Section: Isolation Of Campylobacter From Humansmentioning
confidence: 99%
“…Of particular relevance to food-borne infections is that the growth requirements of C. jejuni do not permit proliferation on contaminated foods under normal storage conditions (Park, 2002). While limited in its ability to proliferate, Campylobacter can survive for extended periods in the environment (Park, 2002) and has been isolated from a number of ecosystems (Altekruse et al, 1999;Bolton et al, 1987;Jones & Bradshaw, 1996;Pearson et al, 1993;Stanley et al, 1998).…”
Section: Introductionmentioning
confidence: 99%